Perception of Identity and Discourse Created With Religious Terminology - Yaman, Haluk (Liberte Yayınları, 2022)
One of the reference points for the originality and different values of identity is the religious sensitivities of identity. While some want to create a perception of identity enclosed with religious sensitivities by using these sensitivities in the spoken language, others present the same perception implicitly in the discourse. Ultimately, this is the different reflections of the responsibility that a person feels as an expression of freedom. The connection between the perception that is intended to be created explicitly or implicitly and political arguments brings together political freedom  and freedom of speech. The variable that stands out among the political arguments is the language of discourse that develops in parallel with the viewpoint of the governments on religion. The discourse language, which includes the doctrines of the institutionalized religion and the traditional doctrines, serves similar purposes in the perception of identity. On the way from traditional religiosity to modern religiosity, the language of discourse makes it difficult to reveal the distinction between intentions and deeds in the perception that is desired to be created through identity. Using the hermeneutic methodology, this study attempts to develop an interpretation of the assumption that the reference symbols of religion in the language of discourse affect the perception of identity.

Kimliğin özgünlüğünden ve farklı değerlerinden bahsederken referans verilen noktalardan birisi kimliğin sahip olduğu dini hassasiyetlerdir. Kimileri bu hassasiyetleri konuşma dilinde kullanarak dini hassasiyetlerle örülü bir kimlik algısı oluşturmak isterken, kimisi de aynı algıyı örtülü şekilde söylem içerisinde sunar. Bu nihayetinde özgürlüğün bir ifadesi olarak insanın kendinde hissettiği sorumluluk halinin farklı şekillerde yansıtılmasıdır. Açık veya örtülü olarak yaratılmak istenen algının siyasi argümanlar ile kurulan bağlantısı, siyasi özgürlük ile söylem özgürlüğünü buluşturmaktadır. Siyasi argümanlar içerisinde öne çıkan değişken ise iktidarların dine bakış açısı paralelinde gelişen söylem dilidir. Kurumsallaşmış bir dinin doktrinleri ile geleneksel doktrinleri içerisine alan söylem dili, kimlik algısında benzer amaçlara hizmet etmektedir. Geleneksel dindarlıktan modern dindarlık üzerine gidilen yolda söylem dili, kimlik üzerinden yaratılmak istenen algıda niyet ve ameller arasındaki ayrımı ortaya koymayı zorlaştırmaktadır. Bu çalışmada, yorumsayıcı (hermeneutik) metodoloji kullanılarak, söylem dilinde yer verilen dini terminolojinin kimlik algısı üzerinde bir etki yarattığına dair bir yorum geliştirilmek istenmektedir.
Dinsel Terminolojiyle Yaratılan Kimlik Algısı ve Söylem
Keywords: Political Science; Siyaset Bilimi